Validation of the French Version of the “Patterns of Activity Measure” in Patients with Chronic Musculoskeletal Pain - Charles Benaim; Bertrand Léger; Philippe Vuistiner; François Luthi (Pain Research and Management)
Background. The “Patterns of Activity Measure” (POAM-P) is a self-administered questionnaire that assesses “avoidance”, “pacing” and “overdoing” activity patterns in chronic pain patients. Objectives. To adapt the POAM-P to French (“POAM-P/F”) and test its validity and reliability in Chronic Musculo-Skeletal Pain patients (CMSP). Methods. We followed the recommended procedure for translation of questionnaires. Five hundred and ninety five inpatients, admitted to a tertiary rehab center in the French-speaking part of Switzerland for chronic pain after orthopedic trauma, were included (sex ratio M/F = 4.36, mean age 43±12). Face, content and criterion validities, internal consistency and reliability were assessed. Data included: TAMPA Scale for Kinesiophobia (TSK), Chronic Pain Coping Inventory (CPCI), Pain Catastrophizing Scale (PCS), Brief Pain Inventory (BPI), Hospital Anxiety and Depression Scale (HADS). Results. Face and content validities were checked during the translation process. Correlations between POAM-P/F-avoidance and TSK, POAM-P/F-pacing and CPCI-pacing, POAM-P/F-overdoing and CPCI-task persistence were highly significant (r>0.3, p<10-2). The three subscales demonstrated excellent homogeneity (Cronbach’s alpha coefficients > 0.8) and test-retest reliability (Intraclass Correlation Coefficients > 0.8). They correlated very differently with the other scales. Discussion and Conclusion. The three POAM-P/F subscales clearly assess different behaviors in CMSP. The POAM-P/F is a suitable questionnaire for classifying French speaking CMSP into avoiders, pacers or overdoers.